PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN DI MATAHARI DEPARTMENT STORE MALANG TOWN SQUARE - Eko Boedhi Santoso; Shinta Maharani Trivena; Nilawati Fiernaningsih (Politeknik Negeri Malang, 2019)
This study aims to determine the effect of Leadership Style and Motivation on employee performance at Matahari Department Store Malang Town Square. This type of research is quantitative. The data used in this study are primary data obtained by distributing questionnaires, interviews. The sampling method using Probability Sampling using Slovin formula, then the samples obtained were 83 respondents. Data analysis in this study uses multiple linear regression method with the help of SPSS 24. The results of this study indicate that Leadership Style has a significant effect on employee performance, motivation has a significant effect on employee performance.